Study of raw material of alfalfa yellow (like-sickle or Romanian) - O. V. Grechana; S. D. Trzhetsinskiy (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2016)
Along with the wide distribution and use of alfalfa grass there is no comprehensive scientific pharmacognosy studies about representatives of the plants of this kind.